IL-6 Baseline Values and Dynamic Changes in Predicting Sepsis Mortality: A Systematic Review and Meta-Analysis - Norberth-Istvan Varga; Iulia Cristina Bagiu; Dan Dumitru Vulcanescu; Voichita Lazureanu; Mirela Turaiche; Ovidiu Rosca; Adrian Vasile Bota; Florin George Horhat (Biomolecules)
Sepsis, a life-threatening condition arising from a dysregulated immune response to infection, is a significant health burden globally. Interleukin-6 (IL-6), an inflammatory cytokine produced by immune cells as a response to infection and tissue damage, plays a key role in the pathogenesis of sepsis. This systematic review and meta-analysis aimed to investigate the association of the baseline plasma levels of IL-6, and the dynamic change in these levels over a timespan of 96 h, with short-term mortality. A systematic literature search was conducted across multiple databases. Studies were included if they assessed the independent prognostic value of IL-6 in adult sepsis patients, used well-defined sepsis criteria, and reported at least one IL-6 measurement. Pooled effect estimates for the association between IL-6 and 28–30-day mortality were determined using logistic regression and AUROC analysis. Thirty-one studies, encompassing 4566 patients, were included. While baseline IL-6 levels and 96 h IL-6 clearance were not significantly associated with mortality risk (pooled OR 1.001, 95% CI 0.999–1.003 and 1.019, 95% CI 0.925–1.112, respectively), AUROC analysis indicated moderate-to-good discriminatory power for both baseline (0.701, 95% CI 0.660–0.742) and 96 h IL-6 clearance (0.828, 95% CI 0.736–0.919) in predicting 28-day mortality. While not a strong independent predictor, IL-6 demonstrates some discriminatory ability, suggesting its potential value in conjunction with other biomarkers.